Embracing risk the changing culture of insurance and responsibility - Baker, Tom, 1959-; Simon, Jonathan, 1959- (Chicago, [Ill.] : University of Chicago Press, 2002)
Offering an original approach to risk, insurance, and responsibility, the provocative and wide-ranging essays in 'Embracing Risk' demonstrate that risk has moved well beyond its origins in the insurance trade to become a central organizing principle of social and cultural life.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Risk -- Sociological aspects; Risk (Insurance); Responsibility; Society; Society & culture: general; Sociology & anthropology; Insurance & actuarial studies; Insurance law